Memahami dan Mengimplementasikan Strategi Pembelajaran Langsung (Direct Instruction) - Gusmaneli Gusmaneli; Widya Febriani; Syaza Sahira (Politeknik Kampar, 2024)
This article discusses the meaning of direct learning strategies. The method used is library research methodology and is qualitative because it collects data from various books and journals. The purpose of this article is to help understand and implement hands-on learning strategies. Based on the explanation above, we can conclude that: First, direct learning strategies are a form and approach to teacher-centered learning (teacher-centered approach). This is said because the teacher plays a very dominant role in this strategy. Second, the stages of implementation and application of direct learning strategies (direct instruction) can be achieved through: Teachers communicating goals, preparing students, demonstrating teacher knowledge and skills, guiding training, checking understanding, providing feedback, and providing further practice and opportunities. Third, the advantages of direct learning are: There is a focus on learning and guidance and control from the teacher. The weakness of this strategy is that it cannot be used with students who have poor listening skills.